Competence of The Authority of Military Police Investigators on Money Laundering Criminal Cases in Connection Cases - Sudarma Setiawan; Madiasa Ablisar; Sunarmi Sunarmi; Mahmud Mulyadi (Locus Journal of Academic Literature Review, 2023)
The investigation of money laundering cases against connexity cases whose perpetrators are "unscrupulous" Indonesian National Army and civilians, currently there is a Constitutional Court Decision No. 15/PUU-XIX/2021 which provides legal certainty for Military Police Investigators to be able to investigate money laundering criminal case against "unscrupulous" Indonesian army who are included as "justiabelen" within the scope of military justice. Previously, the money laundering criminal case could not be continued due to the existence of the Explanation of Article 74 of Law No. 8 of 2010 concerning the Prevention and Eradication of Laundering Crimes. The purpose of this study is to determine and analyze the competence of the authority of military police investigators in the case of money laundering crimes in connexity cases. This research is a descriptive normative legal research, using a statutory approach and a case approach. The results of the study concluded that the Military Justice law can override general laws. The competence of the investigative authority carried out by the Military Police Investigator in the money laundering criminal case against the investigation of the concurrency case can be carried out based on the Decision of the Indonesian Constitutional Court No. 15 / PUU-XIX / 2021, where the Military Police Investigator has obtained mandatory authority based on the law.